Taxonomic status of Podabrus albocaudatus Krefft, 1872 and declaration of Sminthopsis granulipes Troughton, 1932 (Marsupialia: Dasyuridae) as a protected name for the White-tailed Dunnart from Western Australia - Parnaby, Harry; Ingleby, Sandy; Divljan, Anja (Zootaxa, 2015)
The name Sminthopsis granulipes Troughton, 1932 has universally and uncontroversially been used for the White-tailed Dunnart since its description in 1932. We regard the forgotten name Podabrus albocaudatus Krefft, 1872 to be an available name and demonstrate that it is a disused, neglected senior synonym of S. granulipes. The holotype of granulipes Troughton is also likely to be the holotype of Krefft’s albocaudatus and therefore an objective synonym. Consequently, Sminthopsis granulipes Troughton, 1932 is declared a nomen protectum and Podabrus albocaudatus Krefft, 1872 a nomen oblitum, as required by Article 23.9.2 of the International Code of Zoological Nomenclature. This action in no way alters current use of Sminthopsis granulipes for the White-tailed Dunnart but is required to ensure continued nomenclatural stability.